Carbon ion irradiation mobilizes antitumor immunity: from concept to the clinic - Shanghai Liu; Xiangyang He; Siqi Liang; Anqing Wu; Lu Liu; Wentao Hu (Radiation Oncology)
Abstract Carbon ion radiotherapy (CIRT), a type of particle therapy, is at the forefront of clinical oncology treatments due to its superior physical properties and biological performance. Although CIRT has demonstrated outstanding therapeutic outcomes in clinical settings, the biological mechanisms underpinning its effects, particularly its immunogenic potential and the superiority of its induced antitumor immune response compared to photon radiotherapy, remain areas of active investigation. This review summarizes the latest research progress on the mechanisms of antitumor immune responses triggered by CIRT and discusses preclinical and clinical studies related to combined CIRT and immunotherapy (CCIT). Against the backdrop of extensive research and significant clinical efficacy achieved by combining radiotherapy with immunotherapy, this review provides a theoretical foundation for a better understanding of the superior tumor cell-killing effects of CIRT and the underlying immunological mechanisms. Further insights into the factors affecting the efficacy, toxic effects, and developmental limitations of this combination therapy mode will be instrumental in guiding the conduction of CCIT studies.